Peningkatan Kemampuan Membaca Pemahaman Siswa Kelas III Sekolah Dasar melalui Pendekatan Pembelajaran Inovatif : (Studi pada Siswa SD Negeri Kertawaluya II) - Mila Karmila (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the difference in students' reading comprehension ability between innovative and conventional teaching methods. The research uses a quantitative approach with a quasi-experimental design. The sample consists of 30 students, divided into two groups: the experimental group using innovative learning and the control group using conventional learning. Data was collected through a reading comprehension test and analyzed using an independent t-test. The results showed a significant difference between the two groups, with a t-value of 2.419 and a Sig. (2-tailed) value of 0.022, indicating that innovative learning is more effective in improving students' reading comprehension ability compared to conventional learning. These findings suggest that a more interactive and technology-based learning approach can enhance students' understanding. Therefore, innovative learning can be considered more effective in developing students' cognitive abilities.